An empirical investigation of the demand for bananas in Germany - Alison Burrell Burrell; Arne Henningsen (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
We use econometric methods to investigate consumer demand for bananas and for other fruit in Germany. Monthly household survey data for the period 1986-1998 are analysed. Demand for bananas is significantly responsive to own price, suggesting that policy-induced price increases generate the usual dead-weight losses. Demand is also responsive to income changes, indicating that there is scope for further market expansion as incomes grow. There is evidence that other categories of fruit are both gross and net substitutes for bananas.
Keywords: 330